TERNATE MALAY LANGUAGE INTERFERENCE IN INDONESIAN LANGUAGE LEARNING PROCESS - Sasmayunita Sasmayunita; M. Nur Hakim; Rio Sukarno (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2021)
Ternate Malay Language Interference in the Indonesian Language Learning Process. This research was conducted with the aim of explaining the interference of the Ternate Malay language in the Indonesian language learning process for the eighth-grade students of Banau National Junior High School, Ternate, and describing the factors that cause interference in the learning process of Ternate Malay for eighth-grade students of Banau National Junior High School, Ternate. This study used the descriptive qualitative method. The data used are primary data and secondary data. The data sources were 28 students who spoke Ternate Malay. Data collection techniques, namely: observation, interviews, documentation, and speaking. The data analysis technique uses descriptive qualitative which includes the process of data reduction, data presentation, summarizing, and verification. The results of the data analysis concluded that the form of interference in the Ternate Malay language in the Indonesian language learning process, namely: (1) interference in the form of words, sentences, phrases, and clauses and (2) the factors causing interference in the Indonesian language learning process was caused by: habit, influence opponents of speech, students are more comfortable using Ternate Malay, have not realized or used to use Indonesian in the learning process.